Questionnaire into traditional African musical instruments - de Troch, Daniel (International Library of African Music, 1971)
What is understood by a questionnaire? The mere mention of questionnaire has something formidable about it even to a European, however accustomed he may be to indiscreet investigation. In fact the present questionnaire is not a cross-examination but a tool designed simply to remind the investigator of what he may have to ask, so that he will not miss some interesting piece of information
Keywords: Africa; Musical instruments; Research; Ethnology; African Music